2017
DOI: 10.1186/s12859-017-1558-3
|View full text |Cite
|
Sign up to set email alerts
|

Drug voyager: a computational platform for exploring unintended drug action

Abstract: BackgroundThe dominant paradigm in understanding drug action focuses on the intended therapeutic effects and frequent adverse reactions. However, this approach may limit opportunities to grasp unintended drug actions, which can open up channels to repurpose existing drugs and identify rare adverse drug reactions. Advances in systems biology can be exploited to comprehensively understand pharmacodynamic actions, although proper frameworks to represent drug actions are still lacking.ResultsWe suggest a novel pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Several biological and chemical databases for therapeutic and experimental drugs have been constructed. In particular, databases such as the National Institute of Mental Health Psychoactive Drug Screening Programme 9 , Receptoromics 10 , Drug Voyager 11 , PubChem 12 , Ligand Expo 13 , ZINC 14 , STITCH 15 and KEGG DRUG 16 have been developed that integrate diverse information such as compound structures, drug targets, and molecular pathways modulated in a biological system. While these databases provide useful information for drug discovery and repurposing processes, they focus on the chemical and molecular level (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Several biological and chemical databases for therapeutic and experimental drugs have been constructed. In particular, databases such as the National Institute of Mental Health Psychoactive Drug Screening Programme 9 , Receptoromics 10 , Drug Voyager 11 , PubChem 12 , Ligand Expo 13 , ZINC 14 , STITCH 15 and KEGG DRUG 16 have been developed that integrate diverse information such as compound structures, drug targets, and molecular pathways modulated in a biological system. While these databases provide useful information for drug discovery and repurposing processes, they focus on the chemical and molecular level (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies tried to establish mechanisms of drugs for diseases using pathways between the drugs and diseases [ 21 23 ]. We showed that our candidate drugs were more functionally similar to known drugs for diseases than non-candidate drugs, using functional modules obtained from pathways between drugs and diseases.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, genome‐wide expression data can be used to profile the effect of drug activity and discover candidates for drug repurposing . Oh et al have devised a new platform, Drug Voyager, to construct a drug‐ signaling pathways. In this platform, three conceptual levels, “initiation,” “perturbation,” and “destination,” represent the molecular‐level action of a drug.…”
Section: Computational Methods For Cbddmentioning
confidence: 99%